Peningkatan Kompetensi Menyusun Silabus Berbasis Pendidikan Budaya dan Karakter Bangsa Melalui Supervisi Akademik Saat PJJ Bagi Guru SMP 21 Semarang - Suwarno Agung Nugroho (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
In the event of distance learning (PJJ), during the pandemic, teachers are required to be able to compile an appropriate learning syllabus. An educational syllabus based on culture and national character is needed to help the learning process professionally during PJJ. The role of the principal in conducting academic supervision to improve competence in compiling a syllabus for cultural education and national character is a necessity. Based on the problems faced by SMPN 21 Semarang teachers, namely the low competence in compiling a syllabus that is integrated with cultural education and national character during PJJ, it is necessary to find a solution. To overcome the problems mentioned above, school principals need to take actions that must be taken, namely carrying out academic coaching on the preparation of a syllabus that is integrated with cultural education and national character. The lack of provision for teachers in compiling a syllabus based on cultural education and national character needs to be addressed. Based on the results of observations in cycle I compared to the comparison in cycle II regarding the competence of compiling a syllabus based on cultural education and national character for teachers of SMP N 21 Semarang, there is a fairly good increase in competence even though the learning is carried out in PJJ. This can be seen from the recapitulation of observations in cycle II, there is an increase in competence, 10 teachers have been able to compile a syllabus based on cultural education and national character. However, there are still 2 teachers who have not been able to compile a syllabus. Thus, there are 83.3% of teachers who have been able to compile categories both syllabus based on cultural education and national character.The conclusion of this research is through academic supervision when PJJ can improve the competence of compiling a syllabus based on cultural education and national character.